Tracking performance for NCSs with multi-communication constraints. (March 2023) - Hu, Junwei; Zhan, Xisheng; Jiang, Xiaowei; Yan, Huaicheng
Abstract: In this paper, the tracking performance of multiple input multiple output (MIMO) networked control systems (NCSs) with multiple communication constraints is studied. The effects of network induced factors (packet loss and network delay) and basic communication constraints (bandwidth, encoding–decoding and different noise) are considered. By inner–outer factorization and Youla parameterization, the mathematical expressions of the performance of the one-degree of freedom (1DOF) controller and two-degree of freedom (2DOF) controller are obtained, respectively. It shows that internal characteristics and network constraints have different effects on the tracking performance of the plant, and the performance of the 2DOF controller is better than that of the 1DOF controller. Finally, several simulation examples are provided to verify the influence of each constraint. Highlights: The framework of MIMO and multi-communication constraint control system is designed reasonably, many practical constraints such as network induced factors and network inherent constraints are considered. By means of mutual decomposition and Youla parameterization, the mathematical expression of MIMO NCSs tracking performance is obtained, and the quantitative relationship between pole instability characteristics, NMP zero and its direction and constraint parameters is shown. The performance of the system is improved by the encoding-decoding and the 2DOF controller. In addition, our network design is closer to complex practical applications.